Tactile spatial negative priming occurs without feature mismatch. - Frings, C; Mast, F; Spence, C (2014)
Negative priming (NP) refers to fact that people respond more slowly and make more errors when responding to target stimuli that were previously ignored. This phenomenon has also been observed when participants respond to the location, and not only to the identity, of the stimulus. Intriguingly, while roughly the same pattern of results has been observed in the visual, auditory, and tactile modalities when it comes to identity-based NP, the same does not hold true for spatial NP: In particular, feature mismatch seems to be the sole cause of auditory spatial NP, whereas response inhibition would appear to be the sole cause of spatial NP in vision. We conducted a novel tactile variant of the spatial NP task. We investigated whether spatial NP in the tactile modality exists, and further, we investigated whether the pattern of spatial NP in the tactile modality compares with what has been documented previously in vision or audition. Tactile spatial NP was observed, and it was independent of feature mismatch, thereby reflecting a comparable pattern as visual spatial NP. We discuss spatial selection with respect to possible modality-specific processes.